Computational and experimental exploration of morpholine pendent 2-hydrazineyl thiazole: Insights from DFT, ADME profiling, antifungal efficacy and molecular docking analyses - Vishnu A. Adole; I.Antony Danish; J.Jebasingh Kores; J.Winfred Jebaraj; S. Janani; Suresh K. Ghotekar; Rakesh D. Amrutkar (Results in Chemistry)
This work presents an extensive computational investigation of the molecular structure and characteristics of molecule (E)-4-(4-(1-(2-(4-(4-nitrophenyl)thiazol-2-yl)hydrazineylidene)ethyl)phenyl)morpholine. Using Density Functional Theory (DFT) with the B3LYP functional and 6–311++G(d,p) basis set, the molecular structure, Frontier Molecular Orbitals (FMOs), Natural Bond Orbital (NBO) interactions, Noncovalent Interactions (NCI), and stability were investigated. An energy gap (ΔE) of 2.92 eV was found by the FMO analysis, indicating a moderate degree of stability and chemical reactivity. Important information about intramolecular charge transfer (ICT) was revealed by the NBO analysis. Significant interactions between the donor and acceptor, namely involving LP(3)N25 → σ*C24-C26, were confirmed by second-order perturbation energies, yielding a stabilization energy of 12.54 kcal/mol. Significant van der Waals contacts were shown by the NCI analysis, particularly between the thiazole and phenyl rings, indicating regions of steric hindrance. UV–Vis, IR, and NMR simulations were used to forecast spectroscopic characteristics. The functional groups in titled compound were identified using infrared spectroscopy (IR). Chemical shifts were precisely assigned using Nuclear Magnetic Resonance (NMR) analysis. Furthermore, the ADME analysis predicted favorable pharmacokinetic properties. With a zone of inhibition of 10.87 mm, the thiazole derivative demonstrated substantial antifungal effectiveness against Aspergillus flavus. The molecular docking analysis revealed titled compound had a significant interaction with cytochrome P450 EryK. Significant hydrogen and hydrophobic contacts were observed in this interaction, which led to a docking score of −5.28 and a binding free energy of −65.65 kcal/mol.